Environmental Issues and Critical Perspectives Mentioned at Public Service Announcements which are Prepared by Primary School Pre-Service Teachers - Bozdemi̇r, Hafife (Bilge Akademi, 2020)
The aim of this study is to determine how primary school pre-service teachers approach environmental issues via public service announcements and their opinions on them. This study was conducted with case survey model. The study group consisted of 34 primary school pre-service teachers. Data were gathered via public service announcements which are prepared by primary school pre-service teachers and structured interview form. For the analysis of the data, descriptive and content analysis was used. It is determined that pre-service teachers addressed mostly environmental issues about wastes. Primary school pre-service teachers’ opinion is it is more effective to raise awareness if individuals see their behaviors’ negative effects and its results on environment on public service announcements. Content which is not definitive does not make sense to primary school pre-service teachers. They appreciate more if the content is more emotional and unique. For this reason in environmental education, it can be recommended that environmental issues should be reviewed with their different aspects during environmental education. Also it can be recommended that there should be different perspectives about this matter and environmental issues should be associated with real life at environmental education.
Keywords: Alan Eğitimleri; environmental education; environmental issues; public service announcements; primary school preservice teachers; Other Fields of Education; 13. Climate action; 4. Education